(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2021)
In 2020, the tenth democratic and free elections after the fall of the communist regime in Slovakia resulted in a broad coalition government, which obtained its mandate mainly to fight corruption. However, the global pandemic of COVID-19 has fundamentally changed priorities. Indeed, growing dissatisfaction with the governance of the state in early 2021 has led to the organization of a referendum on early parliamentary elections. The article draws attention to the constitutional problems associated with holding such a referendum in the conditions of the Slovak Republic, not only in general, but also, and especially, in times of crisis.